Super-Resolution Imaging of Protein Secretion Systems and the Cell Surface of Gram-Negative Bacteria - Gunasinghe, Sachith D.; Webb, Chaille T.; Elgass, Kirstin D.; Hay, Iain D.; Lithgow, Trevor (Frontiers in Cellular and Infection Microbiology, 2017)
Gram-negative bacteria have a highly evolved cell wall with two membranes composed of complex arrays of integral and peripheral proteins, as well as phospholipids and glycolipids. In order to sense changes in, respond to, and exploit their environmental niches, bacteria rely on structures assembled into or onto the outer membrane. Protein secretion across the cell wall is a key process in virulence and other fundamental aspects of bacterial cell biology. The final stage of protein secretion in Gram-negative bacteria, translocation across the outer membrane, is energetically challenging so sophisticated nanomachines have evolved to meet this challenge. Advances in fluorescence microscopy now allow for the direct visualization of the protein secretion process, detailing the dynamics of (i) outer membrane biogenesis and the assembly of protein secretion systems into the outer membrane, (ii) the spatial distribution of these and other membrane proteins on the bacterial cell surface, and (iii) translocation of effector proteins, toxins and enzymes by these protein secretion systems. Here we review the frontier research imaging the process of secretion, particularly new studies that are applying various modes of super-resolution microscopy.